Analisis Pelaksanaan Pencatatan Petty Cash (Kas Kecil) pada PT. Energy Sakti Sentosa, Pakkat - Wardah T. Simamora; Nurlaila Nurlaila (Universitas Muhammadiyah Enrekang, 2022)
Every company will definitely experience expenses and income (income) that are identical to cash. Therefore, it is necessary to have financial records with the aim of accurately knowing how much income and expenses the company experiences. In addition, by recording the cash, we will find out whether the company is experiencing a profit or a possible loss each period. Therefore, a cash section was formed, which was called petty cash which was signed by the petty cash officer as the person in charge and the functions concerned to directly improve operational efficiency. The company's established operational operating procedures must be followed when managing the relatively simple transactions that need to be recorded. As a result, the author attempts to conduct scientific research on the PT implementation of petty cash records. Energy Sakti Sentosa, Pakkat. This study employs qualitative descriptive methods for data collection, including interviews, observation, and documentation. The study's findings demonstrate that PT has implemented petty cash. Energy Sakti Sentosa, Pakkat is carried out using the imperst method, or fixed fund method. In this method, the amount of the petty cash fund remains constant throughout the duration of the transaction. However, instead of waiting until the end of the period to replenish the petty cash fund, the method used instead replenishes it when the petty cash balance is low. A petty cash fund is also held by the company treasurer when petty cash is used, which can make the treasurer work harder. Implementation procedures and a number of records are used to carry out operational tasks like setting up a petty cash fund in petty cash implementation, and replenishing the petty cash fund.